log(2x-3)=log

Simple and best practice solution for log(2x-3)=log equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for log(2x-3)=log equation:


Simplifying
log(2x + -3) = log

Reorder the terms:
glo(-3 + 2x) = log
(-3 * glo + 2x * glo) = log
(-3glo + 2glox) = log

Solving
-3glo + 2glox = glo

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-1glo' to each side of the equation.
-3glo + -1glo + 2glox = glo + -1glo

Combine like terms: -3glo + -1glo = -4glo
-4glo + 2glox = glo + -1glo

Combine like terms: glo + -1glo = 0
-4glo + 2glox = 0

Factor out the Greatest Common Factor (GCF), '2glo'.
2glo(-2 + x) = 0

Ignore the factor 2.

Subproblem 1

Set the factor 'glo' equal to zero and attempt to solve: Simplifying glo = 0 Solving glo = 0 Move all terms containing g to the left, all other terms to the right. Simplifying glo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-2 + x)' equal to zero and attempt to solve: Simplifying -2 + x = 0 Solving -2 + x = 0 Move all terms containing g to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + x = 0 + 2 x = 0 + 2 Combine like terms: 0 + 2 = 2 x = 2 Add '-1x' to each side of the equation. x + -1x = 2 + -1x Combine like terms: x + -1x = 0 0 = 2 + -1x Simplifying 0 = 2 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| X=52+3y | | -72/g=-8 | | Y-6=3/5(x-1) | | 3/5e-6=2/59e-10)-7 | | a=3n-5 | | 2(f+1)=8 | | Log(17)*289=2 | | 20-(6)= | | (5-3x)(2x+1)= | | -3+a=4 | | 25/x=2.5/4 | | 6(x-2)=3(x+3) | | 1.33/16 | | -2=1-d | | Log(8)*1/64=-2 | | -2+k=-12 | | -4(c-16)=-12 | | -12m+6=4m+2 | | 110+29n= | | 6m+53=m(6+3)+38 | | K-63/3=10 | | Log*10=1 | | x+46=4x+22 | | 3y^2-x^2=9 | | 3(t+17)=6 | | 16.01=3g+3.62 | | (3+4i)+(7-2i)= | | 1.06g-4=0.77 | | x=2lny | | 0=2m^2+9m+4 | | 3y-2/5+2=7 | | 2w^2+w-42=0 |

Equations solver categories